Affective Theory of Mind in Late Adulthood: The Role of Emotion Complexity and Social Relatedness. - Stutesman, Megan G.; Frye, Douglas A. (Experimental Aging Research)
Age-related declines in adult affective theory of mind (AToM) have been discovered. However, AToM measures have not accounted for emotional state complexity involved in AToM. Measures have also not accounted for different types of relationships – friends versus strangers – for which AToM is employed, which is important considering the limited social networks of aging adults. We address these issues and examine the emotion complexity, social-relatedness, and contextual relevance in AToM across adult ages (18–89 years) using a new task and two well-established measures. The new task displayed good structural fit and internal construct validity. Overall, an age-related decline in AToM was found along with an interaction between age and emotion complexity. For all ages, AToM performance was best for complex emotions. However, as age increased, there was more rapid decline in AToM for more complex emotions than for less complex ones. Surprisingly, AToM performance for strangers was better than for social companions. The findings suggest age-related AToM declines are more nuanced than previously understood given that adult age differences are related to emotional state complexity. They indicate that the emotion complexity levels of basic, complex, and self-conscious should be included in AToM assessments. Implications for AToM tasks and development are discussed.